Multiobjective robust H2/H∞ fuzzy tracking control for thermal system of power plant. (October 2018) - Liu, Miao; Dong, Ze
Highlights: A multiobjective robust H 2 / H ∞ fuzzy tracking controller design is proposed for nonlinear system. The multiobjective H 2 / H ∞ fuzzy tracking controller can minimize the H 2 and H ∞ control performance indices simultaneously. Linear matrix inequality-based multiobjective evolution algorithm is studied. Fuzzy H 2 / H ∞ robust tracking control with state observer algorithm is studied. Abstract: In this study, we introduce a multiobjective robust fuzzy H 2 / H ∞ tracking control scheme for nonlinear dynamic superheat temperature system of an ultra-supercritical power plant to guarantee the optimal H 2 and H ∞ reference tracking performance simultaneously. A Takagi–Sugeno fuzzy model is first employed to approximate the nonlinear dynamics of the ultra-supercritical superheat temperature system. Subsequently, the H 2 / H ∞ tracking control design problem is formulated as a multiobjective problem to simultaneously minimize the H 2 control performance index and H ∞ control performance index for the fuzzy system. Then, an indirect method is proposed to solve this multiobjective problem for the multiobjective H 2 / H ∞ fuzzy tracking control design. Next, a linear matrix inequality-based multiobjective evolution algorithm is developed based on a non-dominating sorting scheme to efficiently search the set of Pareto optimal solutions for this multiobjective problem, from which the engineers can select a set of design parameters according to the system performance preferences. In order to improve the applicability to engineering projects, the state observer and error integrator are adopted in the control strategy. Finally, a simulation example of an ultra-supercritical superheat temperature system is presented to illustrate the design procedure and to confirm the robust and optimal tracking performance of the proposed method.